2018
DOI: 10.1136/bmjopen-2017-020313
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle advice to cancer survivors: a qualitative study on the perspectives of health professionals

Abstract: ObjectivesAdoption of healthy lifestyle behaviours has shown promising effectiveness in reducing the high morbidity burden of cancer survivors. Health professionals (HPs) are well suited to provide lifestyle advice but few survivors report receiving guidance from them. This study aimed to explore HPs’ perspective of lifestyle advice (on healthy eating, physical activity, smoking, and alcohol) for cancer survivors.DesignIn-depth semistructured qualitative interviews were conducted by telephone or face to face. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 26 publications
3
64
1
Order By: Relevance
“…If PA roles are assigned sensibly, this may help to accommodate certain barriers to PA promotion that have been reported by healthcare professionals working with cancer patients, e.g. lack of consultation time, or not wanting to overwhelm the patient [67][68][69] ; worry about undermining the relationship with the patient 68 ; and lacking confidence in providing PA advice. 68,70 Reports also suggest that there may be a significant educational need amongst health care professionals in this regard, 70,71 which could be considered a secondary barrier for patients.…”
Section: The Potential For a Bidirectional Facilitative Relationshimentioning
confidence: 99%
“…If PA roles are assigned sensibly, this may help to accommodate certain barriers to PA promotion that have been reported by healthcare professionals working with cancer patients, e.g. lack of consultation time, or not wanting to overwhelm the patient [67][68][69] ; worry about undermining the relationship with the patient 68 ; and lacking confidence in providing PA advice. 68,70 Reports also suggest that there may be a significant educational need amongst health care professionals in this regard, 70,71 which could be considered a secondary barrier for patients.…”
Section: The Potential For a Bidirectional Facilitative Relationshimentioning
confidence: 99%
“…Currently, various unacceptable inequalities exist across Europe regarding cancer care and rehabilitation and reintegration of people with cancer and cancer survivors in social and professional life. Such inequalities include unequal access to curative cancer treatments; extreme variability and accessibility in cancer screening services; lack of patient‐accessible, accurate, and up‐to‐date information; fragmented or missing cancer rehabilitation services; poor governance; major organisational, structural, and fiscal deficits in health planning; and the lack of a citizen‐focused European cancer survivorship plan [addressed in the ECPC position paper ‘Challenging the Europe of disparities in cancer’ (European Cancer Patient Coalition, )] (Table ; Albreht et al ., ; De Angelis et al ., ; European Cancer Patient Coalition, , ,, ,; European Commission, ; European Society for Medical Oncology, ; Kandolf Sekulovic et al ., ; Koutoukidis et al ., ; Luengo‐Fernandez et al ., ; Mehnert et al ., ; Peiró Pérez et al ., ).…”
Section: Patients’ Inequalities Priorities and Innovative Solutionsmentioning
confidence: 99%
“…aims to evaluate the impact of a mobile phone-based, remote-monitoring, symptom-management intervention (the Advanced Symptom Management System, ASyMS) on the delivery of care to people diagnosed with nonmetastatic breast, colorectal or haematologic cancer during chemotherapy and for 1 year after the end of treatment. addressed in the ECPC position paper 'Challenging the Europe of disparities in cancer' (European Cancer Patient Coalition, 2015)](Table 4;Albreht et al, 2017;De Angelis et al, 2014; European Cancer Patient Coalition, 2015, 2017a,b, 2018a European Commission, 2018; European Society for Medical Oncology, 2017;Kandolf Sekulovic et al, 2017;Koutoukidis et al, 2018;Luengo-Fernandez et al, 2013; Mehnert et al, 2013; Peir o P erez et al, 2017).The ECPC has persuaded the participating EU Member States to recognise the need for a Policy Paper on inequalities to complement the CanCon Guide. The ECPC co-authored the CanCon's Policy Paper 'Tackling social inequalities in cancer prevention and control for the European population' (Peir o P erez et al,…”
mentioning
confidence: 99%
“…12 Despite this, research to date among both HCPs and those LWBC consistently shows that few oncology HCPs offer guidance to oncology patients on healthy lifestyle behaviours. [13][14][15][16][17][18][19][20][21] Reported barriers among HCPs in providing health behaviour advice for those Strengths and limitations of this study ► This study provides an insight in therapeutic radiographers' views on all key modifiable health behaviours for those living with and beyond cancer. ► The participants worked in different radiotherapy departments, offering insight into the practices among therapeutic radiographers in the delivery of healthy behaviour advice from a wide range of hospitals.…”
Section: Introductionmentioning
confidence: 98%
“…Open access LWBC, include believing that giving advice was not part of their role, lack of time with patients, lack of referral programmes, lack of resources such as education leaflets for those LWBC and lack of knowledge regarding guidelines and research findings. [16][17][18][19][20][21] A recent qualitative study with 21 oncology HCPs identified that advice on health behaviours provided to those LWBC focussed on general health and controlling side effects, with few HCPs advising on health behaviours in the context of improving survival outcomes. 20 While these studies provide useful insight into the practices and barriers among oncology HCPs the participants within these studies were primarily oncologists and nurses and focussed on the provision of physical activity and weight management advice.…”
Section: Introductionmentioning
confidence: 99%